University entrepreneurship and technology transfer process, design, and intellectual property - Libecap, Gary D. (Advances in the study of entrepreneurship, innovation and economic growth ;, 2005)
This volume of 12 chapters contains some of the latest research on university-based technology transfer, intellectual property issues, and the entrepreneurship program/technology transfer interface. Eleven of the papers are from the Colloquium on Entrepreneurship Education and Technology Transfer held at the White Stallion Ranch, Tucson, Arizona, January 21-23, 2005, organized by the Karl Eller Center, University of Arizona, and funded by the Ewing Marion Kauffman Foundation of Kansas City. Patterns of technology transfer are outlined in papers by Donald Siegel, Phillip Phan, David Mowery, and David Audretsch, Max Keilbach, and Erik Lehmann. They describe the determinants of technology transfer, its impact, and challenges within a university setting. The history of university licensing activity is provided. Intellectual property issues and questions of the relationship between traditional basic university research and applied, potentially commercial research are described in papers by Katherine Strandburg, David Adelman, and Brett Frischmann. The ineffectiveness of university blocking patents in certain areas of the biosciences is discussed, along with broader questions of licensing and ownership. Interdisciplinary university entrepreneurship programs are outlined in papers by Jerry Thursby, Marie Thursby, Thomas Byers and Andrew Nelson, and Arthur Boni and S. Thomas Emerson. The authors detail the approaches taken at four universities to link entrepreneurship programs to technology transfer and technology transfer offices. The insights for adoption elsewhere are valuable. The final chapter by Morton Kamien is an essay on the characteristics and importance of entrepreneurs in the growth of a society.